IMPLEMENTASI KEBIJAKAN PROGRAM PENGELOLAAN SAMPAH DI KOTA BANDUNG PROVINSI JAWA BARAT - Saputra, Ginanjar Wira; Santosa, Pandji; Adiwisastra, Jossy (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
The waste management problem in Bandung City has reached a critical level, marked by daily waste volume exceeding the capacity of the Sarimukti Final Disposal Site (TPA). This condition has prompted the Bandung City Government to implement a series of policies aimed at reducing waste at its source. This study aims to analyze the implementation of waste management program policies in Bandung City, focusing on the